2015
DOI: 10.5851/kosfa.2015.35.3.350
|View full text |Cite
|
Sign up to set email alerts
|

Improved Functional Characteristics of Whey Protein Hydrolysates in Food Industry

Abstract: This review focuses on the enhanced functional characteristics of enzymatic hydrolysates of whey proteins (WPHs) in food applications compared to intact whey proteins (WPs). WPs are applied in foods as whey protein concentrates (WPCs), whey protein isolates (WPIs), and WPHs. WPs are byproducts of cheese production, used in a wide range of food applications due to their nutritional validity, functional activities, and cost effectiveness. Enzymatic hydrolysis yields improved functional and nutritional benefits i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 85 publications
2
53
0
1
Order By: Relevance
“…On the other hand, the structure of the proteins is altered during hydrolysis since buried hydrophobic groups are exposed and free to interact. It is proposed that noncovalent interactions, mainly electrostatic and hydrophobic, are major interacting forces since they promote aggregation and subsequent gel settings (Fuke et al, 1985, Otte et al, 1996, Otte et al, 1997, Jeewanthi et al, 2015. However, Kuipers et al (2005) concluded based on their findings that the aggregation is not a simple balance between repulsive electrostatic and attractive hydrophobic interactions, but much more complex.…”
Section: Gelling Propertiesmentioning
confidence: 99%
“…On the other hand, the structure of the proteins is altered during hydrolysis since buried hydrophobic groups are exposed and free to interact. It is proposed that noncovalent interactions, mainly electrostatic and hydrophobic, are major interacting forces since they promote aggregation and subsequent gel settings (Fuke et al, 1985, Otte et al, 1996, Otte et al, 1997, Jeewanthi et al, 2015. However, Kuipers et al (2005) concluded based on their findings that the aggregation is not a simple balance between repulsive electrostatic and attractive hydrophobic interactions, but much more complex.…”
Section: Gelling Propertiesmentioning
confidence: 99%
“…Whey proteins technological benefits have also been analysed for being added to food and drinks, in order to increase solubility, gelation, emulsification, foam and tamponade capabilities to the formulations (Jeewanthi et al ., ). Industry also has been seeking to develop products with better functional attributes (Tan et al ., ), and with high sensory quality, demanding studies about new ingredients like whey proteins (Zavareze et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…At the beginning, many industries considered it a residue, which needs adequate treatment for its disposal, but this product presents important minerals, such as calcium, besides a significant amount of essential amino acids and high protein value (Bosi et al, 2013), which makes it a very relevant ingredient that could be used in different food (Ganju & Gogate, 2017), Whey proteins technological benefits have also been analysed for being added to food and drinks, in order to increase solubility, gelation, emulsification, foam and tamponade capabilities to the formulations (Jeewanthi et al, 2015). Industry also has been seeking to develop products with better functional attributes (Tan et al, 2015), and with high sensory quality, demanding studies about new ingredients like whey proteins (Zavareze et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in solubility after hydrolysis may be result of liberation of low molecular weight peptides and increase in number of ionizable groups (NH 4 ? , COO -), which leads to increase in hydrophilicity and net charge, thus enhancing solubility by promoting interactions between hydrolysate and water (Jeewanthi et al 2015). The increase in WHC of WPH is the result of exposure of unexposed hydrophobic amino acids and their interactions with surface hydrophobic amino acids or similar peptides.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to increased solubility of WPH (Flanagan and Fitzgerald 2002;Jeewanthi et al 2014). Limited hydrolysis leads to increased solubility due to the reduced molecular weight and the increased hydrophilicity resulting from the increase in free carboxyl and amine groups (Jeewanthi et al 2015). Foegeding et al (2002) also reported that heat stability of proteins can be improved upon partial hydrolysis due to loss of secondary structure and thus contributing to reduced structural changes upon heating.…”
Section: Apparent Viscosity Profilementioning
confidence: 99%